Philosophy of Body: Embodiment, Perception, and Understanding Other Minds - Godwins, Jude (Advances in Social Sciences Research Journal, 2023)
The lived body, as an embodied self, lives, breathes, perceives, acts and reasons (Drew Leder, 1990, 1-8). The imaginative, with its schematic structures, has a role in thought (Lakoff, 1987, 275; Johnson 1987, 76,) even as we show preference for the biological and psychological turn. The problem of other minds is about how we come by the power to understand other people, comprehend their behaviours, know their intentions, and discern their mental processes. In the Husserlian phenomenology, we come to know and recognize the other through bodily movement. The kinaesthetic experience of having a grip on its surrounding world leads the ego into the knowledge and recognition of the other (Husserl, 1937, 16, § 62). We can take this kinaesthetic experience of knowing the other through motor behaviour farther. Following an empathic understanding that comes from our shared motor resonance system, we understand others when their motor behaviour is put in a narrative framework (Gallagher, 2006). We admit, as Gallagher does, that neither a “cold theoretical logic” (of folk psychology ) nor a “self-controlled simulation” (of simulation theory ) replaces the powers associated with the primary- and secondary inter-subjectivity that attend the way we interact with others, first as babies and later as children (Gallagher, 2006, 12).